Persepsi Guru tentang Pembelajaran Kooperatif dalam Pendidikan IPS - Sunaryanto Sunaryanto (Jurnal Ilmu Pendidikan, 2016)
This study is intended to describe teachers' understanding and implementation as well as their thinking of cooperative learning in social studies education. The researcher worked with 15 primary school teachers in Victoria, Australia. Data were collected by using an open ended questionaire, observation of classroom practice and non-structured inverview following the observation. Then, the data were analysed by using content analysis method. The findings suggest that the participants generally understand positive interdependence and social interaction, and group debriefing is important elements of cooperative learning. Teacher do not pay much attention to individual accountability and reward system. Social skills are the important achievement of cooperative learning implementation